Ultrasound-driven coating for promoting vascular tissue repair and its preparation method and application
Prepare ultrasonic driver to drive the repair of vascular tissue repair through static spinning technology, and use ultrasonic stimulation to regulate the release of anticoagulants to solve the problem of poor biological compatibility of the existing cardiovascular implant intervention. Repair effects and safety.
Patent Information
- Application Number
- CN202411290144.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-14
AI Technical Summary
The existing cardiovascular interventional devices have poor biocompatibility, obvious side effects and single treatment effects, making it difficult to effectively promote vascular tissue repair.
The electrostatic spinning technology is used to prepare an ultrasonic driving coating for the repair of vascular tissue. The coating contains piezoelectric materials and anticoagulants. It can adjust the release of anticoagulants through ultrasonic stimulation to promote the proliferation and migration of endothelial cells.
It improves the biocompatibility of the cardiovascular implant intervention equipment, reduces the risk of thrombosis, promotes the regeneration and repair of vascular endothelial cells, and enhances the treatment effect and safety of the equipment.
Smart Images

Figure CN118806993B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of medical biological coating materials, and in particular relates to an ultrasound-driven coating for promoting vascular tissue repair, and a preparation method and application thereof. Background Art
[0002] With the rapid development of modern society, the rapid acceleration of the pace of life and the prevalence of unhealthy living habits, cardiovascular disease has become a major health threat worldwide. Although medical technology is constantly improving, there are still many key issues and challenges in the treatment of cardiovascular diseases. Cardiovascular implants, represented by artificial heart valves, artificial small blood vessels, occluders and vascular stents, are widely used in the clinical treatment of cardiovascular diseases. Taking vascular stents as an example, although the existing drug-coated stents can effectively prevent vascular restenosis, the drugs in their coatings may inhibit the normal growth of endothelial cells, leading to delayed or incomplete vascular endothelialization, thereby increasing the risk of late thrombosis; although the fully degradable stents have certain biocompatibility and degradability, their mechanical stability during the degradation process is insufficient, which may cause the stent to lose its supporting function in the late stage of degradation, thereby affecting the treatment effect. Therefore, developing materials or surface coatings with better biocompatibility, reducing immune and inflammatory reactions, and exploring surface functionalization technologies to promote faster endothelialization and device integration, in addition, further improving the safety, effectiveness and applicability of cardiovascular implants, are still the problems that need to be solved in the current treatment of cardiovascular diseases.
[0003] In recent years, multifunctional surface implantable devices have become one of the frontiers of cardiovascular disease treatment research. The introduction of a variety of functional coatings and materials on the surface of the device makes it have a wider range of biological activity and therapeutic potential. At present, most of the research is mainly based on chemical modification and biological modification. After implantation, it is easy to respond to the complex environment in the body (such as immune response, inflammatory response, protein adsorption), thus bringing the risk of failure. These reactions may lead to material degradation, reduced mechanical properties or loss of biological activity. Intelligent materials are leading the development trend of multifunctional cardiovascular implantable devices. Intelligent materials can respond to external stimuli (such as electricity, light, heat or ultrasound) to achieve dynamic drug release and cell selectivity. This responsiveness enables intelligent materials to adjust their behavior according to specific needs and external environmental conditions during treatment, providing more precise and personalized treatment plans. The application of this material is expected to bring significant advantages in targeted therapy, reducing side effects and improving treatment effects, especially in complex and changeable biological environments. However, the limited penetration depth of light makes it difficult to act on deep tissues or the internal structure of cardiovascular implantable devices, which limits its widespread use in the application of cardiovascular implantable devices; in addition, thermal stimulation can induce inflammatory reactions or destroy cell structures. Summary of the invention
[0004] In view of the above-mentioned prior art, the present invention discloses an ultrasound-driven coating that promotes vascular tissue repair and its preparation method and application, so as to solve the technical problems of poor biocompatibility, obvious side effects and single therapeutic effect of the coating of central vascular implant interventional devices in the prior art.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is: to provide a method for preparing an ultrasound-driven coating that promotes vascular tissue repair, which comprises the following steps:
[0006] S1: dissolving the piezoelectric material and the anticoagulant in a solvent, heating and centrifuging to obtain an electrospinning solution;
[0007] S2: The electrospinning solution is spun by an electrospinning device to obtain highly oriented nanofibers;
[0008] S3: The highly oriented nanofibers are dried and annealed; the drying temperature is 37-50°C, the drying time is 1-3 days; the annealing temperature is 80-150°C, and the annealing time is 1-24 hours.
[0009] Furthermore, in step S1, the piezoelectric material is an organic piezoelectric polymer; the anticoagulant is an anticoagulant drug or a copper salt; the solvent is a mixture of one or two of N,N-dimethylformamide, dimethyl sulfoxide, tetrahydrofuran, acetic acid, trifluoroethanol and acetone, and when the solvent includes two components, the volume ratio between the components is 5~9:1~5.
[0010] Furthermore, the organic piezoelectric polymer is poly-L-lactic acid, polyacrylonitrile, polyvinylidene fluoride or polyvinylidene fluoride trifluoroethylene; the anticoagulant drug is heparin, warfarin, bivalirudin, apixaban, rivaroxaban or dabigatran etexilate; and the copper salt is copper chloride, copper oxide or copper carbonate.
[0011] Furthermore, the material-liquid ratio of the piezoelectric material, the anticoagulant and the solvent is 1 g: 22~50 mg: 4~8 mL.
[0012] Furthermore, in step S1, the heating temperature is 37-100° C., the heating time is 0.5-12 h; the centrifugal speed is 1000-10000 rpm, and the centrifugal time is 1-60 min.
[0013] Furthermore, in step S2, the positive high voltage of the spinning process is 10-30 KV, the injection rate is 0.1-2 mL / h, the injection needle is 10-20 cm away from the receiving device, and the shaft speed is 500-5000 rpm.
[0014] Furthermore, before drying in step S3, the nanofibers are soaked in an ethanol solution with a concentration of 50-100 wt % for a soaking time of 20-45 min.
[0015] The invention also discloses the application of the above coating driven by ultrasound to promote vascular tissue repair in the preparation of medical implant materials.
[0016] Furthermore, the medical implant material is a cardiovascular implant intervention device, and the cardiovascular implant intervention device is a vascular stent, a heart occluder, an artificial heart valve or an artificial small blood vessel.
[0017] By adjusting the external ultrasonic frequency, the release of anticoagulants in the coating can be effectively regulated in time and space. The ultrasonic power is 1~10W / cm 2 , ultrasonic frequency is 1~10MHz, and ultrasonic time is 1~60min.
[0018] The beneficial effects of the present invention are:
[0019] 1. The ultrasound-driven coating for promoting vascular tissue repair prepared by the present invention using electrospinning technology has good biocompatibility. The cardiovascular implantable device prepared using the coating has uniform nanofibers in the coating and a highly oriented topological structure on the surface of the coating, which is beneficial to guiding endothelial cells to migrate and proliferate in a certain direction during the angiogenesis process, thereby reducing the risk of thrombosis.
[0020] 2. The coating in the present invention can respond to external ultrasonic signals, activate the coating through ultrasonic energy transfer and vibration, and trigger the targeted release of anticoagulants. This is a physical process. Ultrasonic waves do not change the chemical properties of the drug or coating. In addition, the piezoelectric output of the coating and the time and dosage of drug release in the coating can be controlled by controlling the frequency of external ultrasonic waves. Ultrasonic stimulation can also promote the proliferation and migration of vascular endothelial cells, and inhibit the proliferation of smooth muscle cells, thereby accelerating the repair of damaged vascular walls and restoring normal functions. In addition, ultrasonic stimulation can inhibit inflammatory responses by regulating the signal transduction pathways of cells.
[0021] 3. The ultrasonically driven coating for promoting vascular tissue repair prepared by the present invention can be used to prepare cardiovascular implantable interventional devices. The piezoelectric material in the coating can give the device an active adjustment function. When the device is subjected to external hemodynamic pressure, it can generate electric charges, which act on the blood vessel wall through electrical stimulation, which helps cell proliferation and migration, thereby promoting endothelial cell regeneration and repair. This adaptive adjustment ability helps to improve the biocompatibility of cardiovascular implantable interventional devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a SEM image of the coating that promotes vascular tissue repair by ultrasound in Example 1;
[0023] Figure 2 This is a time-voltage diagram of the coating that promotes vascular tissue repair by ultrasound in Example 1;
[0024] Figure 3 This is the UV absorption spectrum of rivaroxaban;
[0025] Figure 4 The cell fluorescence staining images of the coating cell activity test in Example 1 and Comparative Example 1;
[0026] Figure 5 The SEM images of the coatings in Example 1 and Comparative Example 1 after the arteriovenous shunt experiment;
[0027] Figure 6 This is a SEM image of a vascular stent prepared with the coating in Example 1 after an abdominal aorta vascular bypass experiment. DETAILED DESCRIPTION
[0028] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.
[0029] Example 1
[0030] A method for preparing an ultrasound-driven coating that promotes vascular tissue repair, the method comprising the following steps:
[0031] S1: Add 1.5 g polyvinylidene fluoride powder, 37.5 mg rivaroxaban powder and 7.5 mL N, N-dimethylformamide / acetone mixed solvent into a 15 mL centrifuge tube, the volume ratio of N, N-dimethylformamide to acetone is 6:4, then place the centrifuge tube in a 60°C water bath for heating for 1 h, and then centrifuge the centrifuge tube at 4200 rpm for 15 min to obtain a uniform electrospinning solution;
[0032] S2: The electrospinning solution was transferred into a 10 mL syringe and placed on the syringe pump of the electrospinning machine. The receiving method of electrospinning was to nest the stainless steel drum on a rotating shaft of matching diameter and rotate and collect. During the electrospinning process, the positive high voltage was 15 KV, the distance from the syringe needle to the receiving end was 15 cm, the injection rate was 0.5 mL / h, and the rotating shaft speed was 2000 rpm. After the electrospinning was completed, nanofibers were obtained on the surface of the stainless steel drum.
[0033] S3: Soak the nanofibers in a 50wt% ethanol solution for 20 minutes. After taking them out, dry them in a vacuum drying oven at 37°C for 3 days to remove residual organic solvents. Then place them in a 100°C oven for high-temperature annealing. The nanofibers are obtained after annealing for 6 hours.
[0034] Example 2
[0035] A method for preparing an ultrasound-driven coating that promotes vascular tissue repair, the method comprising the following steps:
[0036] S1: Add 1g of poly-L-lactic acid, 22mg of dabigatran etexilate powder and 7mL of dimethyl sulfoxide / acetone mixed solvent into a 15mL centrifuge tube, with the volume ratio of dimethyl sulfoxide to acetone being 5:5, then heat the centrifuge tube in a 37°C water bath for 0.5h, and then centrifuge the centrifuge tube at 3000rpm for 30min to obtain a uniform electrospinning solution;
[0037] S2: The electrospinning solution was transferred into a 10 mL syringe and placed on the syringe pump of the electrospinning machine. The electrospinning receiving method was to nest the polylactic acid-based roller on a rotating shaft of matching diameter and rotate and collect. During the electrospinning process, the positive high voltage was 20 KV, the distance from the syringe needle to the receiving end was 18 cm, the injection rate was 0.8 mL / h, and the rotating shaft speed was 1500 rpm. After the electrospinning was completed, nanofibers were obtained on the surface of the polylactic acid-based roller.
[0038] S3: Soak the nanofibers in an 80wt% ethanol solution for 45min. After taking them out, dry them in a vacuum drying oven at 50°C for 1d to remove residual organic solvent. Then, place them in an oven at 150°C for high-temperature annealing. The nanofibers are obtained after annealing for 6h.
[0039] Example 3
[0040] A method for preparing an ultrasound-driven coating that promotes vascular tissue repair, the method comprising the following steps:
[0041] S1: Add 0.8 g polyvinylidene fluoride trifluoroethylene powder, 32 mg copper chloride powder and 6.4 mL tetrahydrofuran / acetone mixed solvent into a 10 mL centrifuge tube, the volume ratio of tetrahydrofuran to acetone is 5:1, then place the centrifuge tube in a 65°C water bath for 12 h, and then centrifuge the centrifuge tube at 10000 rpm for 1 min to obtain a uniform electrospinning solution;
[0042] S2: The electrospinning solution was transferred into a 10 mL syringe and placed on the syringe pump of the electrospinning machine. The receiving method of the electrospinning was to nest the cobalt-chromium alloy roller on a rotating shaft of matching diameter and rotate to collect. During the electrospinning process, the positive high voltage was 10 KV, the distance from the syringe needle to the receiving end was 10 cm, the injection rate was 0.1 mL / h, and the rotating shaft speed was 500 rpm. After the electrospinning was completed, nanofibers were obtained on the surface of the cobalt-chromium alloy roller.
[0043] S3: Soak the nanofibers in a 100wt% ethanol solution for 30 minutes. After taking them out, dry them in a vacuum drying oven at 37°C for 3 days to remove residual organic solvents. Then, place them in a 150°C oven for high-temperature annealing. The nanofibers are obtained after annealing for 1 hour.
[0044] Example 4
[0045] A method for preparing an ultrasound-driven coating that promotes vascular tissue repair, the method comprising the following steps:
[0046] S1: Add 1.5 g poly-L-lactic acid powder, 75 mg apixaban powder and 6 mL trifluoroethanol / acetic acid mixed solvent into a 10 mL centrifuge tube, the volume ratio of trifluoroethanol to acetic acid is 9:5, then heat the centrifuge tube in a 100°C water bath for 2 h, and then centrifuge the centrifuge tube at 1000 rpm for 60 min to obtain a uniform electrospinning solution;
[0047] S2: The electrospinning solution was transferred to a 10 mL syringe and placed on the syringe pump of the electrospinning machine. The receiving method of electrospinning was to nest the nickel-titanium alloy roller on a rotating shaft of matching diameter and rotate to collect. During the electrospinning process, the positive high voltage was 30 KV, the distance from the syringe needle to the receiving end was 20 cm, the injection rate was 0.6 mL / h, and the rotating shaft speed was 2500 rpm. After the electrospinning was completed, nanofibers were obtained on the surface of the nickel-titanium alloy roller.
[0048] S3: Soak the nanofibers in an 80wt% ethanol solution for 30 minutes. After taking them out, dry them in a vacuum drying oven at 50°C for 1 day to remove residual organic solvents. Then place them in an oven at 80°C for high-temperature annealing. The nanofibers are obtained after annealing for 24 hours.
[0049] Example 5
[0050] A method for preparing an ultrasound-driven coating that promotes vascular tissue repair, the method comprising the following steps:
[0051] S1: Add 1 g of polyacrylonitrile powder, 40 mg of copper oxide powder and 8 mL of N,N-dimethylformamide into a 20 mL centrifuge tube, then heat the centrifuge tube in a 60 ° C water bath for 8 h, and then centrifuge the centrifuge tube at 5000 rpm for 40 min to obtain a uniform electrospinning solution;
[0052] S2: The electrospinning solution was transferred into a 10 mL syringe and placed on the syringe pump of the electrospinning machine. The electrospinning receiving method was to nest a polytetrafluoroethylene-based roller on a rotating shaft of matching diameter and rotate and collect. During the electrospinning process, the positive high voltage was 15 KV, the distance from the syringe needle to the receiving end was 15 cm, the injection rate was 2 mL / h, and the rotating shaft speed was 5000 rpm. After the electrospinning was completed, nanofibers were obtained on the surface of the polytetrafluoroethylene-based roller.
[0053] S3: Soak the nanofibers in a 60wt% ethanol solution for 40 minutes. After taking them out, dry them in a vacuum drying oven at 40°C for 2 days to remove residual organic solvents. Then place them in a 120°C oven for high-temperature annealing. The nanofibers are obtained after annealing for 6 hours.
[0054] Example 6
[0055] A method for preparing an ultrasound-driven coating that promotes vascular tissue repair, the method comprising the following steps:
[0056] S1: Add 1 g of polyvinylidene fluoride powder, 30 mg of heparin and 6 mL of acetone to a 10 mL centrifuge tube, then heat the centrifuge tube in a water bath at 80 °C for 8 h, and then centrifuge the centrifuge tube at 5000 rpm for 20 min to obtain a uniform electrospinning solution;
[0057] S2: The electrospinning solution was transferred into a 10 mL syringe and placed on the syringe pump of the electrospinning machine. The electrospinning receiving method was to nest a polytetrafluoroethylene-based roller on a rotating shaft of matching diameter and rotate and collect. During the electrospinning process, the positive high voltage was 15 KV, the distance from the syringe needle to the receiving end was 15 cm, the injection rate was 1.5 mL / h, and the rotating shaft speed was 4000 rpm. After the electrospinning was completed, nanofibers were obtained on the surface of the polytetrafluoroethylene-based roller.
[0058] S3: Soak the nanofibers in a 60wt% ethanol solution for 30 minutes. After taking them out, dry them in a vacuum drying oven at 40°C for 2 days to remove residual organic solvents. Then place them in a 90°C oven for high-temperature annealing. The nanofibers are obtained after annealing for 12 hours.
[0059] Example 7
[0060] A method for preparing an ultrasound-driven coating that promotes vascular tissue repair, the method comprising the following steps:
[0061] S1: Add 1.5 g polyvinylidene fluoride powder, 60 mg warfarin and 10 mL dimethyl sulfoxide / acetone mixed solvent into a 20 mL centrifuge tube, the volume ratio of dimethyl sulfoxide to acetone is 9:1, then place the centrifuge tube in a 60°C water bath for 10 h, and then centrifuge the centrifuge tube at 8000 rpm for 10 min to obtain a uniform electrospinning solution;
[0062] S2: The electrospinning solution was transferred into a 10 mL syringe and placed on the syringe pump of the electrospinning machine. The electrospinning receiving method was to nest a polytetrafluoroethylene-based roller on a rotating shaft of matching diameter and rotate and collect. During the electrospinning process, the positive high voltage was 15 KV, the distance from the syringe needle to the receiving end was 18 cm, the injection rate was 2 mL / h, and the rotating shaft speed was 5000 rpm. After the electrospinning was completed, nanofibers were obtained on the surface of the polytetrafluoroethylene-based roller.
[0063] S3: Soak the nanofibers in a 60wt% ethanol solution for 40 minutes. After taking them out, dry them in a vacuum drying oven at 45°C for 2 days to remove residual organic solvents. Then place them in a 10°C oven for high-temperature annealing. The nanofibers are obtained after annealing for 18 hours.
[0064] Comparative Example 1
[0065] A method for preparing a coating, the method comprising the following steps:
[0066] S1: Add 500 mg of polyvinylidene fluoride powder, 25 mg of rivaroxaban powder and 5 mL of N,N-dimethylformamide / acetone mixed solvent into a 1.5 mL centrifuge tube, the volume ratio of N,N-dimethylformamide to acetone is 6:4, then place the centrifuge tube in a 60°C water bath for heating for 1 h, and then centrifuge the centrifuge tube at 4200 rpm for 15 min to obtain a uniform electrospinning solution;
[0067] S2: The electrospinning solution was transferred into a 10 mL syringe and placed on the syringe pump of the electrospinning machine. The receiving method of electrospinning was to nest the stainless steel drum on a rotating shaft of matching diameter and rotate and collect. During the electrospinning process, the positive high voltage was 15 KV, the distance from the syringe needle to the receiving end was 15 cm, the flow rate was 0.5 mL / h, and the rotating shaft speed was 2000 rpm. After the electrospinning was completed, nanofibers were obtained on the surface of the stainless steel drum.
[0068] S3: Soak the nanofibers in a 50wt% ethanol solution for 20 minutes. After taking them out, dry them in a vacuum drying oven at 37°C for 3 days to remove residual organic solvents. Then place them in a 100°C oven for high-temperature annealing. The nanofibers are obtained after annealing for 6 hours.
[0069] Experimental example
[0070] The coating properties obtained in the embodiments of the present invention are similar, and the performance of the related products is described by taking Embodiment 1 as an example.
[0071] 1. Structural test
[0072] The sample prepared in Example 1 was subjected to electron microscopy scanning, and the SEM image was as follows: Figure 1 As shown, it can be seen from the figure that the sample surface has a highly oriented topological structure.
[0073] 2. Ultrasonic response performance test
[0074] ① Fix the sample prepared in Example 1 on the sample fixture to ensure that the ultrasonic wave can evenly irradiate the sample surface, turn on the ultrasonic instrument, and set the ultrasonic power of the ultrasonic instrument to 3W / cm 2 , the ultrasonic frequency is 2MHz, and the voltage measuring instrument is started at the same time to start recording the value and change trend of the output voltage within 5 minutes of ultrasound. The results are as follows Figure 2 As shown in the figure, it can be seen that the sensitivity and stability of the coating's ultrasonic response are excellent.
[0075] ② Take 2 portions (50 mg) of the coating prepared in Example 1 and immerse them in 3 mL of PBS buffer solution. One group is ultrasonicated at 37°C for 1 min with an ultrasonic power of 1 W / cm 2 , the ultrasonic frequency was 1 MHz, and the other group was not subjected to ultrasonic treatment; after immersion for 24 hours, the concentration of rivaroxaban in the PBS buffer solution was determined using an ultraviolet spectrophotometer (PerkinElmer LAMBDA 850+), and the detection wavelength of rivaroxaban was set at 248 nm. The spectrum is shown in Figure 3 As shown, it can be seen from the spectrum that the absorbance of rivaroxaban in the ultrasound group is significantly greater than that in the non-ultrasound group, which indicates that ultrasound can drive the nanofiber coating loaded with rivaroxaban in the present invention to release more rivaroxaban.
[0076] 3. Piezoelectric performance test
[0077] The samples prepared in Examples 1 to 5 and Comparative Example 1 were fixed on a piezoelectric 33 On the tester, manually apply appropriate pressure to the sample to ensure that the pressure is applied evenly and stably. Use a charge amplifier to measure the charge Q generated on the sample surface after the pressure is applied. Use a strain gauge to measure the strain ε of the sample under the applied pressure. A is the cross-sectional area of the sample in the direction of force. Calculate the piezoelectric constant d according to the following formula: 33 .
[0078]
[0079] The calculation results are shown in Table 1. It can be seen from the table that the piezoelectric constant of the sample prepared in Comparative Example 1 is significantly smaller than that in the embodiment, which means that the amount of charge generated when subjected to external force is less, which limits the performance of the cardiovascular implantable device prepared using it. When subjected to hemodynamic pressure, less charge is generated, which is not conducive to cell proliferation and migration. At the same time, the efficiency of converting electrical energy into mechanical energy is low, which is not conducive to the morphological adjustment of cardiovascular implantable devices and the targeted release of anticoagulants.
[0080] Table 1
[0081]
[0082] 3. Biocompatibility Test
[0083] ① The biocompatibility of the ultrasound-driven coating for promoting vascular tissue repair in the present invention was evaluated by cell activity. Human umbilical vein endothelial cell line (HUVECs) was revived from liquid nitrogen and cultured in a cell culture incubator at 37°C and 5% CO2. When the cells grew to 80-90% confluence, the cells were digested with trypsin and the cell suspension was collected. Then, the cells were cultured at 1×10 ^4 The density of cells / well was co-cultured with the coating prepared in Example 1 and Comparative Example 1 for 3 days respectively to allow cell adhesion and proliferation; 5 mg / mL FDA (fluorescein diacetate) solution (solvent: DMSO) was diluted to 5 µg / mL using PBS buffer, and then 500 µL of the diluted FDA solution was added to each well to stain the cells, and then incubated at 37°C for 15 minutes in the dark to ensure that FDA was fully hydrolyzed into fluorescein by the esterase in the cells. After staining; the cells were gently washed twice with PBS to remove excess staining solution, and then the fluorescence signal of the cells was observed under an inverted fluorescence microscope using the FITC channel (excitation wavelength 488 nm, emission wavelength 530 nm), as shown Figure 4 As shown in the figure, living cells emit bright green fluorescence, while dead cells or cells with low metabolic activity have weak or no fluorescence, indicating that the coating of the present invention has good biocompatibility.
[0084] ② Arteriovenous shunt experiment
[0085] A stainless steel-based vascular stent loaded with the coating in Example 1 was prepared, and the preparation method was as follows: the electrospinning solutions in Example 1 and step S1 of Comparative Example 1 were respectively transferred to 10 mL syringes, and then placed on the injection pumps of the electrospinning machine respectively. The receiving device for electrospinning was a stainless steel-based roller. During the electrospinning process, the positive high voltage was 15 KV, the distance from the syringe needle to the receiving end was 15 cm, the injection rate was 0.5 mL / h, and the shaft speed was 2000 rpm. After the electrospinning was completed, a surface loaded with highly oriented nanofibers was obtained, and then it was dried in a vacuum drying oven at a temperature of 37°C for 3 days to remove residual organic solvents, and then placed in a 100°C oven for high-temperature annealing, and the stent was obtained after annealing for 6 hours.
[0086] Experimental process: The left carotid artery and right jugular vein of an anesthetized healthy male New Zealand white adult rabbit (2.5 kg) were separated, and a vascular stent was placed between the artery and vein to form an arteriovenous extracorporeal circulation. After 1 hour, the vascular stent was taken out and cleaned to remove blood stains and impurities, and the vascular stent was fixed with paraformaldehyde and dehydrated with alcohol with a concentration gradient of 70-100wt%. The thrombus conditions on the surfaces of the coatings loaded in Example 1 and Comparative Example 1 were observed by scanning electron microscopy. The SEM images are shown in FIG. Figure 5 As shown, no obvious thrombus is formed on the surface of the coating of Example 1, indicating that the coating of the present invention can significantly reduce the risk of platelet adhesion and thrombus formation.
[0087] ③ Abdominal aortic stent implantation experiment
[0088] Experimental process: The prepared stainless steel-based vascular stent loaded with the coating in Example 1 was implanted into the abdominal aorta of anesthetized healthy male New Zealand white rabbits (weight 2.5 kg). Two weeks later, the stent with surrounding vascular tissue was removed and fixed with paraformaldehyde for 1 week. After dehydration, the cell morphology of the neointima on the inner surface of the stent was observed by scanning electron microscopy. SEM images are shown in Figure 2. Figure 6 As shown, the brighter area in the image is the boundary of the cells. The results show that the metal stent is covered by the new endothelium, which once again shows that the stent has good biocompatibility and reduces the risk of thrombosis in the stent. It can also be seen from the figure that in the early stage of stent implantation, the cells on the inner surface of the new endothelium are irregular; in addition, the surface of the stent can be completely covered by a layer of densely and regularly arranged endothelial cells (pebble-shaped) in two weeks, further confirming that the coating on the surface of the stent is conducive to the rapid promotion of directional growth of endothelial cells.
[0089] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.
Claims
1. An application of an ultrasound-driven coating for promoting vascular tissue repair, characterized in that: The coating driven by ultrasound to promote vascular tissue repair is used to prepare medical implant materials; the medical implant materials are cardiovascular implant intervention devices, and the cardiovascular implant intervention devices are vascular stents, heart occluders, artificial heart valves or artificial small blood vessels; the ultrasonic power responded by the medical implant materials is 1-10W / cm 2 , the ultrasonic frequency is 1-10MHz; the preparation method of the ultrasonically driven coating for promoting vascular tissue repair is prepared by the following steps: S1: dissolving a piezoelectric material and an anticoagulant in a solvent, heating and centrifuging to obtain an electrospinning solution; the piezoelectric material is an organic piezoelectric polymer, and the organic piezoelectric polymer is poly-L-lactic acid, polyacrylonitrile, polyvinylidene fluoride or polyvinylidene fluoride trifluoroethylene; S2: using an electrospinning device to spin the electrospinning solution to obtain highly oriented nanofibers; the positive high voltage of the spinning process is 10-30KV, the injection rate is 0.1-2mL / h, the injection needle is 10-20cm away from the receiving device, and the shaft speed is 500-5000rpm; S3: The highly oriented nanofibers are dried and annealed to obtain the nanofibers; before drying, the nanofibers are immersed in an ethanol solution with a concentration of 50-100 wt% for 20-45 min; the drying temperature is 37-50°C and the drying time is 1-3 d; the annealing temperature is 80-150°C and the annealing time is 1-24 h.
2. The use of the coating for promoting vascular tissue repair by ultrasound drive according to claim 1, characterized in that: The anticoagulant is an anticoagulant drug or a copper salt; the solvent is a mixture of one or two of N,N-dimethylformamide, dimethyl sulfoxide, tetrahydrofuran, acetic acid, trifluoroethanol and acetone. When the solvent includes two components, the volume ratio between the components is 5~9:1~5.
3. The use of the coating for promoting vascular tissue repair by ultrasound drive according to claim 2, characterized in that: The anticoagulant drug is heparin, warfarin, bivalirudin, apixaban, rivaroxaban or dabigatran etexilate; the copper salt is copper chloride, copper oxide or copper carbonate.
4. The use of the coating for promoting vascular tissue repair by ultrasound drive according to any one of claims 2 to 3, characterized in that: The material-liquid ratio of the piezoelectric material, the anticoagulant and the solvent is 1 g: 22~50 mg: 4~8 mL.
5. The use of the coating for promoting vascular tissue repair by ultrasound drive according to claim 1, characterized in that: In step S1, the heating temperature is 37-100° C., the heating time is 0.5-12 h; the centrifugal speed is 1000-10000 rpm, and the centrifugal time is 1-60 min.
Citation Information
Patent Citations
Artificial blood vessel capable of simulating natural blood vessel to release electric signals, and preparation method thereof
CN111938867A
Bone implantation prosthesis with drug-loaded piezoelectric coating as well as preparation method and application of bone implantation prosthesis
CN118436852A